2013
DOI: 10.3109/0142159x.2013.778391
|View full text |Cite
|
Sign up to set email alerts
|

Patient-led training on patient safety: A pilot study to test the feasibility and acceptability of an educational intervention

Abstract: Background: Training in patient safety is an important element of medical education. Most educational interventions on patient safety training adopt a 'health-professional lens' with limited consideration on the impact of safety lapses on the patient and their families and little or no involvement of patients in the design or delivery of the training. Aims: This paper describes a pilot study to test the feasibility and acceptability of implementing a patient-led educational intervention to facilitate safety tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 16 publications
0
50
0
4
Order By: Relevance
“…However, patients who have received Web-based educational intervention reported better outcomes than patients who received traditional education, such as face-to-face sessions [24]. Patient-centered patient safety intervention has not been widely studied, but one study on patient safety intervention among patients reported the feasibility and acceptability of face-to-face intervention [25]. Considering the effectiveness of Web-based interventions in previous patient education, utilizing an online program will provide more promising results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients who have received Web-based educational intervention reported better outcomes than patients who received traditional education, such as face-to-face sessions [24]. Patient-centered patient safety intervention has not been widely studied, but one study on patient safety intervention among patients reported the feasibility and acceptability of face-to-face intervention [25]. Considering the effectiveness of Web-based interventions in previous patient education, utilizing an online program will provide more promising results.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of patients' contributions to their safety and the prevention of errors [25] has been emphasized for more than a decade in other advanced countries. For example, there have been many initiatives in patient safety and regarding patients as partners for patient safety outside of Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The full details of the intervention were published previously 28 29. Patient and carers, recruited from the National Patient Safety Agency, Action for Victims of Medical Accidents and advertisements in the local press, were included if they had experience of suffering harm or error to themselves or their families during healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…Patient and carers, recruited from the National Patient Safety Agency, Action for Victims of Medical Accidents and advertisements in the local press, were included if they had experience of suffering harm or error to themselves or their families during healthcare. Four preparatory Patient Learning Journey workshops prepared the patient group for the teaching programme 29. The workshops created a confidential supportive environment where the group could comfortably share their experiences, bond with each other, identify key aspects to include within the narrative, and adopt a learner-centred approach 22…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation